2011
DOI: 10.1029/2010ja016418
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional shape of the magnetopause: Global MHD results

Abstract: [1] The numerical results from a physics-based global magnetohydrodynamic (MHD) model are used to examine the relationship between the shape and size of the magnetopause and the solar wind conditions. The magnetopause location is identified by tracing three-dimensional streamlines through the simulation domain and is fitted by simple analytical functions. The resulting model is applicable for approximating magnetopause location for dipole tilt angle ∼0°and interplanetary magnetic field (IMF) B X and B Y = 0 nT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 39 publications
1
71
1
Order By: Relevance
“…However, at present they rather add to the confusion. In particular, Lu et al (2011) found that larger negative IMF B z causes the tailward magnetopause to shrink, contrary to the empirical models by both Shue et al (1998) and Lin et al (2010). Such a strange result is most likely due to the actual boundary studied in that work being not the magnetopause proper, but the fluopause , located inward from the magnetopause and gradually converging towards the plasma sheet owing to the dawn-dusk electric field caused by IMF B z < 0.…”
Section: Magnetopause Shape and The Imf 'Penetration'contrasting
confidence: 51%
“…However, at present they rather add to the confusion. In particular, Lu et al (2011) found that larger negative IMF B z causes the tailward magnetopause to shrink, contrary to the empirical models by both Shue et al (1998) and Lin et al (2010). Such a strange result is most likely due to the actual boundary studied in that work being not the magnetopause proper, but the fluopause , located inward from the magnetopause and gradually converging towards the plasma sheet owing to the dawn-dusk electric field caused by IMF B z < 0.…”
Section: Magnetopause Shape and The Imf 'Penetration'contrasting
confidence: 51%
“…Although they can predict widely divergent magnetopause locations for the same solar wind conditions (Samsonov et al 2016), global magnetohydrodynamic simulations all indicate that the solar wind dynamic pressure and north/south component of the IMF are the most important factors determining magnetopause location (Lu et al 2011). As illustrated in the top panel of Fig.…”
Section: Earth's Magnetopausementioning
confidence: 99%
“…Most empirical magnetopause models [e.g., Sibeck et al, 1991;Petrinec and Russell, 1996;Shue et al, 1997;Kawano et al, 1999] also adopted the hypothesis that magnetopause is rotational symmetric about the aberrated Sun-Earth line and has a rounded section at magnetotail. Lu et al [2011] developed a numerical three-dimensional magnetopause model considering the impact of IMF B z and solar wind dynamic pressure (D p ) on the shape of magnetopause. They showed that the dayside magnetopause shape in the yz plane is an oval elongated along the y direction, and the magnetotail magnetopause is an oval elongated along the z direction.…”
Section: 1002/2013ja019257mentioning
confidence: 99%